Strategi Guru dalam Mengatasi Kejenuhan Belajar Siswa pada Mata Pelajaran Ekonomi untuk Meningkatkan Hasil Belajar Siswa Kelas X MA Al Ma’arif Tulungagung - Dwi Lutfhiana Nur Janah (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Economics is a science that can be identified as an interactive process that equips students with knowledge, skills, and attitudes related to economic phenomena that occur in everyday life in society. However, in this economics learning does not always run smoothly there are also factors that cause student boredom that they feel, one of which is often sleepy and looks bored when the teacher teaches this lesson, Because the teaching methods applied by the teacher are not interesting enough for students, they become bored and have difficulty understanding the material presented. Therefore, teachers must develop appropriate methods so that students do not feel bored. This study aims to determine 1) The reasons behind the physical and mental conditions of class X students at MA Al Ma'arif Tulungagung during economics learning. 2) The approach taken by teachers to overcome student boredom in learning economics in class X MA Al Ma'arif Tulungagung. 3) The level of effectiveness of the teacher's approach in dealing with boredom in learning economics to improve student learning outcomes at MA Al Ma'arif Tulungagung. This study uses a qualitative approach with a descriptive design. To collect data, this study applies observation, interview, and documentation techniques.